2021
DOI: 10.3390/su13105345
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Economic Impacts of the Energy Transition

Abstract: There is currently no consensus regarding whether or not renewable energies are capable of supplying all of our energy needs in the near future. To shed new light on this controversy, this paper develops a methodology articulating a macroeconomic model with two sectors (energy and non-energy) and an energy model that is able to calculate the maximum potentials of solar and wind energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For instance, in the case of electricity, a 'Losses (of Electricity)' industry is added, that takes as input 'Electricity (before Losses)' and produces 'Electricity (after Losses)'. We then apply equation (10) to the product 'Electricity (after Losses)'.…”
Section: Accounting For Losses and Energy Self Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the case of electricity, a 'Losses (of Electricity)' industry is added, that takes as input 'Electricity (before Losses)' and produces 'Electricity (after Losses)'. We then apply equation (10) to the product 'Electricity (after Losses)'.…”
Section: Accounting For Losses and Energy Self Consumptionmentioning
confidence: 99%
“…Tackling the climate change emergency requires a considerable change in the structure of energy systems and to replace fossil fuels by renewable energy sources. Concerns have been raised recently regarding the net energy [4][5][6] and macroeconomic implications of the energy transition [7][8][9][10][11] , because renewable energy systems have been traditionally thought to have substantially lower EROIs than fossil fuel-based energy systems 12 . Recent works have shown that such an understanding may be misguided, due to inconsistent comparisons whereby the primary-stage fossil fuel EROIs (fuels extracted, quantified at the mine or well mouth) are compared to the final-stage renewable energy EROIs (energy carrier delivered to the end user) 13,14 .…”
mentioning
confidence: 99%
“…Final energy demand is expected to increase by about 1.8% per year, driven by the need for energy to support higher living standards, and accompanied by massive energy efficiency gains. There are studies such as (Dupont et al, 2021) present scenarios that are based on the possibility of an absolute decoupling between the production of goods and services and energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…and the CO 2 emissions released by their ever-escalating use threaten every aspect of human societies as well as a large part of the living world [2,3]. In this context, a rapid and global transition to low-carbon energy sources is deemed a necessity, although not without scrutiny of its feasibility [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%